Effect of interferon therapy on glucose metabolism in children with chronic hepatitis B - Kuloğlu, Zarife; Berberoğlu, Merih; Kansu, Aydan; Demirçeken, Fulya; Doğanci, Tümay; Ocal, Gönül; Girgin, Nurten (The Turkish Journal of Pediatrics, 2010)
The aim of this study was to investigate the effect of interferon (IFN)-alpha treatment on glucose metabolism in children with chronic hepatitis B (CHB). Forty children with CHB received IFN 10 MU/m2 for six months. Oral glucose tolerance test, anti-insulin and anti-glutamic acid decarboxylase (GAD) antibody, fasting plasma C-peptide and insulin (FPI), postprandial insulin, homeostasis model assessment of insulin resistance (HOMA-IR), HOMA-cell, and glucose/insulin ratio (G/I) were measured before and after treatment. The last four parameters were also evaluated in healthy controls (n=42). In patients, fasting plasma glucose (FPG) and HOMA-IR levels were significantly lower than in controls (p = 0.001 and p = 0.020, respectively). There was a strong correlation between degree of liver disease and FPG. Two patients had hyperinsulinemia. HOMA-IR was suppressed in 7 patients enough to indicate increased sensitivity. FPI of 13 patients and HOMA-cell of 9 patients were lower than the minimum level of controls, features compatible with beta-cell hypofunction. Frequency of glucose metabolism abnormalities was not different before and after therapy. After therapy, only 1 patient developed anti-GAD antibody, and FPI of 8 children and HOMA-cell level of 9 children were lower than the minimum level of controls. Hyperinsulinemia was persistent in the same patients. We demonstrated that HBV-infected children had insulin sensitivity; however, no adverse effects of IFN on glucose homeostasis were seen.